State Responsibility in Inclusive Consumer Protection for Persons with Disabilities - Yuanitasari, Deviana (Pusat Analisis Keparlemenan Badan Keahlian Setjen DPR RI, 2025)
Consumer protection is an integral part of the state's responsibility to ensure the fulfillment of citizens' rights. However, consumers with disabilities often do not receive equal treatment in accessing safe, appropriate products, services, and information. This article aims to examine the extent to which the state plays a role in ensuring inclusive consumer protection policies for persons with disabilities, particularly from a human rights perspective. Using a normative juridical approach and analysis of both national policies and international standards such as the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD), the article finds that consumer protection for persons with disabilities in Indonesia remains fragmented and lacks a foundation in substantive justice principles. The state is required not only to regulate generally but also to actively affirm and supervise business actors to ensure the provision of accessible products and services. Furthermore, consumer literacy for persons with disabilities requires more serious state intervention through rights-based affirmative policies. This article recommends strengthening technical regulations, integrated supervision, and the development of inclusive service standards to promote equitable and non-discriminatory consumer protection.